Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.022
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Forgiveness on Psychological Well-Being in Adolescents: A Review

Abstract: Psychological well-being is a multidimensional concept to which individuals carry out their psychological functions positively. One of the factors that influence psychological well-being is forgiveness. Teenagers who have the ability to forgive things that hurt their feeling can have a prosperous psychological impact. The purpose of this article is to find out how forgiveness affects adolescent psychological well-being. The method used in this article is a literature review by using research journals published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…However, more clinical studies and researches are needed on these issues. Just like gratitude, psychological well-being also nurtures positive emotions in individuals and thus, they feel satisfaction and happiness in their lives (Wulandari & Megawati, 2019). It can be said that individuals with high levels of psychological well-being are more forgiving than individuals with low levels.…”
Section: Result Discussion and Suggestionsmentioning
confidence: 99%
“…However, more clinical studies and researches are needed on these issues. Just like gratitude, psychological well-being also nurtures positive emotions in individuals and thus, they feel satisfaction and happiness in their lives (Wulandari & Megawati, 2019). It can be said that individuals with high levels of psychological well-being are more forgiving than individuals with low levels.…”
Section: Result Discussion and Suggestionsmentioning
confidence: 99%
“…Forgiveness is beneficial for enhancing stress coping abilities. Engaging in forgiveness interventions equips individuals with effective strategies to navigate through negative experiences (Wulandari & Megawati, 2020). Particularly, forgiveness proves to be impactful in anger management.…”
Section: Aims Of Interventionsmentioning
confidence: 99%
“…Forgiveness is defined as the process of recognizing an offender's faults and attempting to repair one's emotional wounds while also developing new relationships in the future (Wulandari & Megawati, 2020). A meta-analysis of forgiveness interventions suggested that forgiveness can help an individual deal with various types of psychological problems (Sandage, Crabtree, & Bell, 2019).…”
Section: Forgiveness Therapy Influence On Emotions and Decisions To F...mentioning
confidence: 99%